Ketika Lirik Menjelma Visual: Membongkar Semiotika Saussure dalam Video Klip Lagu “Hena” - Hilda Ma'iisya Salma; Mustari Mustari (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2026)
This study reveals how lyrics and visuals are interconnected in shaping meaning. This study aims to analyze the music video for the song “Hena” popularized by Humood Alkhudher and Mehdi Mozayine using Ferdinand de Saussure’s semiotic approach. The method used is descriptive qualitative analysis by applying four main concepts of Saussurean semiotics, namely signifier–signified, langue–parole, synchronic–diachronic, and syntagmatic–paradigmatic, which are examined through differential relations. The result of this study indicates that the music video for the song “Hena” constructs meaning through the integration of signifiers between lyrics and visuals that mutually reinforce the signified. The meaning conveyed is not singular but dynamic, emerging from the interplay between childhood memories, friendship, familial affection, and hopes for the future. This music video also represents Arab cultural values as a language, yet presents them through personal and emotional expressions as a parable that resonates with the universal experiences of its audience. While affirming synchronic meaning in a contemporary context, it also incorporates diachronic elements that depict the passage of time from childhood to adulthood as part of the process of emotional identity formation. The conclusion of this study indicates that the meaning of “Hena” is constructed through the dynamic relationship between lyrics and visuals, in which both reinforce, negotiate, and contrast the message. Thus, Saussurean semiotics opens a new perspective on the construction of meaning in contemporary popular music.